Characteristic Analysis of High-Speed Permanent Magnet Synchronous Motor - Kyoung Bang, Tae; Hun Shin, Kyung; In Lee, Jeong; Han, Cheol; Kook Cho, Seong; Young Choi, Jang (International Journal of Engineering and Technology, 2018)
Background/Objectives: This paper presents characteristic analysis of High-SpeedPermanent Magnet Synchronous Machine (High-Speed PMSM) by using FEM (Finite Element Method) tools. The High-Speed PMSM need the protective tube with non-magnetic materials that protect the scattering of permanent magnet, it is necessary that analyzed about mechanical analysis.Methods/Statistical analysis: For preventing and improving, the fracture of the rotor of High-Speed PMSM, it is important that analyzed characteristic of mechanical stress, it should not be analyzed that occurred the fracture and decreased the performance, since the structure of rotor. However, structure analysis is usually performed by using FEM, which need the big amount of time consuming. Therefore, in this paper is derived the mechanical stress of rotor by using analytical method of stress.Findings: The results of the stress analysis are compared with the results of FEM analysis that validated the analytical method of stress analysis. Based on the results of the analysis, an analytical model was fabricated. Through the experiments, the presence of rotor breakage was examined and the performance was measured.Improvements/Applications: It can be applied to stress analysis and characterization of superhigh speed machine through the analysis methods presented in this paper.Â Â